Educación y Desarrollo - Villalobos Hernández, Teresita (2002)
This article deals with the relationship between the governing class and education as ideological machinery at the State service. It also addresses the issue of education as an economic, political and social development factor. Education turns into an instrument at the service of democracy to form a tamed people whom the political class in government has tried, by means of imported models, to adjust them to the diverse socio-historical realities of our country.